2013
DOI: 10.1063/1.4817826
|View full text |Cite
|
Sign up to set email alerts
|

The doping of the polyimide alignment layer by semiconductor quantum dots

Abstract: We investigated the electro-optic properties of nematic liquid crystal cells oriented by polyimide (PI) layer doped with 3.5 nm semiconductor quantum dots (QDs) CdSe/ZnS at concentrations of 0.05 and 0.1 wt. %. It is shown that doping PI orienting layer by QDs reduces the permittivity and the phase delay, as well as increases the electrical resistance of the cells. Also we observed deceleration of liquid crystal (LC) optical response caused by the screening effect of the orienting layer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This was attributed to the self-organization of the q-dots. In a more recent study [44], CdSe/ZnS q-dots were incorporated into the homogeneously aligning polyimide layer of NLC cells. The authors confirmed reduced ε, ΔΦ, slower optical response, and increased electrical resistance with no visible changes in V th .…”
Section: Effects Of Quantum-dots On Liquid Crystal Physical Propertiesmentioning
confidence: 99%
“…This was attributed to the self-organization of the q-dots. In a more recent study [44], CdSe/ZnS q-dots were incorporated into the homogeneously aligning polyimide layer of NLC cells. The authors confirmed reduced ε, ΔΦ, slower optical response, and increased electrical resistance with no visible changes in V th .…”
Section: Effects Of Quantum-dots On Liquid Crystal Physical Propertiesmentioning
confidence: 99%
“…In general, the long‐chain organic ligands are used to protect/functionalize the surface and increase the steric repulsion of semiconductor QRs. It was observed that in the QR/LCM composite systems, the interaction of the QR ligands with the molecular LC matrix often leads to topological defects in the QRs/LCP composite films, which also depends on the concentrations of both nanoparticles and LCM in solution . On one hand, for the low concentration of LC molecules, the orientational forces do not notably contribute to the aggregation process, but the interaction due to the change of the order parameter near the QR surface plays an important role .…”
Section: Introductionmentioning
confidence: 99%